ChemInform Abstract: Formamidobisabolene‐Based Derivatives from a Sponge Axinyssa sp. Issue 44 (4th November 2014) - Cheng, Wei; Liu, Dong; Zhang, Fengying; Zhang, Qingying; Pedpradab, Patchara; Proksch, Peter; Liang, Hong; Lin, Wenhan
Abstract 12 new formamidobisabolene derivatives, named axinyssines A‐L, are isolated from a Chinese sponge Axinyssa sp.